INFLUENCE OF PHYTOPATHOGENIC FUNGI ON QUALITY PARAMETERS OF GREEN BEAN SEEDS IN A FIVE-YEAR PERIOD - Zivkovic, Ivana; Damnjanović, Jelena; Poštić, Dobrivoj; ŠTRBANOVIĆ, Ratibor; Stanisavljević, Rade; PERIĆ, Vesna; TABAKOVIĆ, Marijenka (Journal on Processing and Energy in Agriculture, 2023)
Green beans are among the most essential legumes because of their nutritional value. In this paper, the quality parameters of two varieties of green beans (GB1 and GB2) on the territory of Smederevska Palanka. The energy germination and total germination were the highest in the first observed year and amounted to 63% and 88% for GB1, respectively. For GB2 the energy germination and total germination (2018) were 71% and 75%, respectively. A significant decline in total germination was determined in 2020. and amounted to 75% for GB1 and 67% for GB2( p0.05). The impact of phytopathogenic fungi on green beans was reflected in the reduction of total germination, and therefore in seed quality and yield.
Keywords: effects, germination, phytopathogenic